As mudanças políticas na Atenção Primária à Saúde brasileira e suas implicações para a atenção psicossocial em um município paraibano - Vieira, Dandara Virgínia Machado (2024)
Primary Health Care (PHC) is characterized as the main entry point to Brazil’s Unified Health System (SUS), offering universal, comprehensive, and free access to health services. Psychosocial Care (AP, in Portuguese) in this context holds a strategic position due to its potential to provide longitudinal care that takes into account the individual's particularities and the territory in which they are located. In a country with continental dimensions and social, economic, and cultural disparities, it is important to understand how public health policies are implemented in small municipalities, taking into account their unique characteristics and needs. This study aims to identify the impacts of political changes in Primary Health Care (PHC) in the municipality of Cuité / PB and their repercussions on Psychosocial Care (AP) from 2012 to 2022. It was a qualitative and exploratory research, of the case study type, with data collection conducted through semi-structured interviews and document analysis. The participants in the study were Nurses and Community Health Agents (ACS, in Portuguese) linked to the Family Health Strategy (ESF, in Portuguese) in the municipality of Cuité / PB. Municipal Health Plans (PMS, in Portuguese) and Annual Management Reports (RAG, in Portuguese) developed between 2012 and 2022 were also analyzed. The data produced were analyzed using the Content Analysis technique proposed by Minayo. All stages of the research were conducted in accordance with the ethical principles and information security guidelines established in Resolution 466/2012 of the National Health Council (CNS). This study resulted in the three articles that make up this dissertation. It was concluded that the Mental Health (MH) care provided by PHC is strongly impacted by changes in public policies and needs to be reoriented to provide assistance that is more aligned with the needs of the territory. However, in the studied context, barriers exist from the planning stage in the management tools, as the goals set for AP are largely focused on medium and high complexity services. This results in isolated and incipiente practices in PHC, with weaknesses observed in the planning and execution of MH collective actions, in user adherence, in the performance of professionals working in the ESF, and in the coordination of care. The findings allow for an analysis of the potential of the territory, daily practices, and health workers, supporting the commitment of management and professionals in transforming the reality through the handling of local complexities.